The Potential of Corn Cobs for Bio-CNG Production and Fermented Feed, and Circular System Marketing to Support a Residue-Free Circular Economy - Mimin Aminah; Rindang; RT Risyahadi; B Purwanto; Dian Anggraeni; HB Surbakti; Suryahado; Gelar Satya Budhi (Jurnal Penelitian Pendidikan IPA, 2026)
The increasing volume of corn cob waste in Indonesia poses environmental challenges and reflects underutilized biomass with potential economic value. This study examines the conversion of corn cobs into Bio-CNG through anaerobic digestion and the utilization of fermentation residues as livestock feed within a circular economy framework. The novelty lies in integrating energy production, feed generation, and circular system marketing in a single agro-based model. A laboratory experimental study using a 3×3 factorial Completely Randomized Design (CRD) was conducted, employing Biomethane Potential Tests (BMP) with rumen and methanogenic inoculums at different temperatures and fermentation times (2–6 days). Gas production and digestate composition were analyzed using standard methods, including proximate analysis. Results show substrate degradation up to 55.34%, methane production reaching 3.82% (rumen microbes, 39°C) and 10.79% (methanogenic basis), and total gas production up to 10.29%. Digestate quality improved, with protein increasing from 4.95% to 7.39% and TDN from 53.34% to 55.42%, indicating suitability as ruminant feed. The study is limited to laboratory-scale and short fermentation duration. Practically, this model can support integrated agroenergy systems in rural areas. In conclusion, corn cobs offer significant potential as a dual resource for renewable energy and livestock feed, supporting sustainable circular agriculture.